A mixed-methods evaluation of hepatitis B knowledge, attitudes, and practices among migrant women in Thailand - Bierhoff, M; Hashmi, AH; Pateekhum, C; Jiraporncharoen, W; Wiwattanacharoen, W; Paw, MK; Nosten, FH; Rijken, MJ; Van Vugt, M; McGready, R; Angkurawaranon, C (BioMed Central, 2021)
Background Globally 90 % of transmission of Hepatitis B virus (HBV) is from mother-to child and occurs predominantly in resource limited countries where the prevalence of HBV is high. Transmission could be interrupted by timely vaccinations but coverage remains problematic in these areas. Low knowledge or awareness of HBV may play a part in low vaccination coverage. This study examines the provision of antenatal care counselling with a focus on HBV in two different regions of northern Thailand, Sarapee Hospital (SH), Chiang Mai, and Shoklo Malaria Research Unit (SMRU), Tak Province. Methods A mixed-methods sequential explanatory study design was used to evaluate antenatal services for migrants. Cross-sectional knowledge, attitude and practice (KAP) surveys were conducted immediately after counselling at first ANC contact, at 3–6 months after first ANC contact and at delivery. Surveys provided quantitative data, and qualitative methods included observations, focus group discussions (FGD) and in-depth interviews (IDI); analysed thematically to explore concepts of knowledge and understanding, attitude and practice of pregnant women and providers. Results Between September-2019 and May-2020, 757 women participated to KAP surveys, and 31 observations of counselling, 16 FGD and 9 IDI were conducted. KAP surveys showed in spite of low knowledge about HBV transmission, infection, or vaccination (correct response: SH 5.7 %, 9/157; SMRU 34.0 %, 204/600), most women (≥ 93 %, either site) understood they were screened for HBV and were willing to vaccinate infants for HBV. In explaining KAP survey results, qualitative analysis suggests counselling should: use the appropriate language; be tailored to the local health literacy level, provide only pertinent information, be repeated over the antenatal period; and attempt to ensure patient privacy (where possible). Programme effectiveness benefits from positive attitudes to screening and vaccinations and a high level of trust in the providers nevertheless participants provided good suggestions for improvements of the service. Conclusions Limited knowledge of HBV among migrant women can be improved by counselling that emphasizes actionable knowledge such as vaccination schedule. Key improvements to the counselling process include training counsellors to conduct interactive counselling sessions in the woman’s language, using appropriate visual aids and timely repetition over the course of the antenatal period.